New Assessment on CFCs Tropospheric Concentration Levels Measured in Terra Nova Bay (Antarctica) - F. Bruner; MAIONE, MICHELA; MANGANI, FILIPPO (International Journal of Environmental Analytical Chemistry, 1996)
Data concerning tropospheric levels of some chlcrofluorocarbons and other halogenated hydrocarbons are reported. These are referred to atmospheric samples collected during the 1993/94 Austral Summer Antarctic Campaign in Terra Nova Bay. Samples collected in Stainless Steel canisters were analyzed in our laboratory by gas chromatography-electron capture detection (GC-ECD). A comparison with data obtained in previous campaigns is reported as well.